1954
DOI: 10.1098/rspa.1954.0197
|View full text |Cite
|
Sign up to set email alerts
|

The heat transport and spectrum of thermal turbulence

Abstract: In this paper a theoretical investigation is made of various properties of the steady-state inhomogeneous turbulent convection of heat in a fluid between horizontal conducting surfaces. An upper limit to the heat transport is found subject to the constraint that some minimum eddy size exists which is effective in this transport. The spectrum of convecting motions, the mean thermal gradients at each point and the eddy conductivity are then determined in terms of the minimum eddy size. The relation between the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 458 publications
(103 citation statements)
references
References 3 publications
5
97
0
1
Order By: Relevance
“…which is attributed to the marginal stability of the thermal boundary layer (33). Low Pr fluids such as liquid metals are more This article is a PNAS Direct Submission.…”
Section: Heat Transfer Regimesmentioning
confidence: 99%
“…which is attributed to the marginal stability of the thermal boundary layer (33). Low Pr fluids such as liquid metals are more This article is a PNAS Direct Submission.…”
Section: Heat Transfer Regimesmentioning
confidence: 99%
“…There are two well-known Nu ∼ Ra α scaling regimes of RBC heat transfer that are accessible with our experiments. One classical prediction, first theorized by Malkus (1954), is the α = 1/3 relation. Malkus' arguments apply to systems containing vigorous convective mixing, where the bulk fluid becomes isothermal and the time-averaged temperature gradients are localized to thin thermal boundary layers adjacent to the top and bottom of the fluid layer.…”
Section: Rayleigh-bénard Convection (Rbc)mentioning
confidence: 99%
“…argue that boundary layer physics controls rotating convective heat transfer in water. By assuming that Malkus' (1954) marginal boundary layer arguments hold in a rapidly rotating system, they develop theoretical arguments predicting that rotating convective heat transfer scales steeply:…”
Section: Rotating Convectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such decompositions can then be used to construct rigorous bounds on flow quantities of interest, consistently with imposed dynamic and kinematic constraints, using conventional techniques of the calculus of variations. Kerswell (1997Kerswell ( , 1998Kerswell ( , 2001) demonstrated that this method produces the complementary variational problem to the earlier approach pioneered by Howard (1963Howard ( , 1972Howard ( , 1990 and Busse (1969aBusse ( , b, 1970Busse ( , 1978, developing ideas originally proposed by Malkus (1954Malkus ( , 1956.…”
Section: Introductionmentioning
confidence: 99%